International Financial Institutions : Dealing with New Global Challenges. (per Jacobson lecture, 2005)
This paper discusses how international financial institutions (IFIs) can deal with new global challenges. The paper highlights that surveillance is the primary responsibility of the IMF. To make it more effective, more attention should be paid to long-term, structural developments that, if left unaddressed, can over time create intractable rigidities and obstacles to growth. These include labor market rigidities, the consequences of demographic trends such as aging, and even the accumulation of international reserves. The interrelations between countries and the systemic impact of policies should also be a key focus of surveillance.